Efficient and Secure SMS Encryption Technique using Elliptic Curve Cryptography - Bhowmick, Anirban (International Journal of Computer Sciences and Engineering, 2015)
Data security over the cellular network is critical. Mobile phones have provided operators with immense facilities at the cost of data privacy. Without ensuring data concealment, communication should be avoided. This makes cryptography an evolving research area. In this paper, the authors propose an asymmetric encryption system which maintains data confidentiality and integrity of the text message throughout the mobile network. In the proposed system, the text message is encrypted before being transmitted over the network. Most of the traditional encryption techniques are computationally intensive. Accordingly, elliptic curve cryptography has been employed to encrypt the text message as it permits efficient use of mobile’s limited resources like memory and processor. One of the key flaws in Short Message Service (SMS) is that it does not provide end-to-end security. The original text is revealed to the utility provider for a short duration of time which can be a reason for misuse. The system proposed offers this much needed data privacy.